The Use of Student Teams-Achievement Divisions Method (STAD) to Improve Listening Comprehension of The Second Grade Student of SMKN 1 Demak in The Academic Year 2019/2020 - Zaenul Wafa (Journalistics: Journal of English Teaching and Applied Linguistics, 2021)
This study is to explore the use of STAD (Student Teams-Achievement Division) to improve listening comprehension. The participants are the second grade students of SMKN 1 Demak which consists of 34 students. This research design is classroom action research. It is aimed to improve students’ participation and comprehension in listening. This research was done in six meetings with the different types of material. There are two cycles in every cycle include two meetings; those are cycle I, and cycle II. The data collection techniques used in this research are documentation and test, the researcher took a test of their improvement in each cycle. In the mean of preliminary assessment was 6.9, in the first meeting of cycle I was 7.3, the second meeting was 7.6 then in cycle II; the first meeting was 7.8, the second meeting was 8.0 and the final assessment was 8.4. The result of the research showed that the students’ listening comprehension skill improves significantly and the students also enjoyed in teaching listening comprehension using STAD